The role of dipole structure and their interaction on the electromechanical and actuation performance of homogeneous silicone dielectric elastomers. (28th February 2019) - Sun, Haibin; Liu, Xueying; Yan, Haichao; Feng, Zhanbin; Yu, Bing; Ning, Nanying; Tian, Ming; Zhang, Liqun
Abstract: Grafting polar groups onto elastomer chains has proven to be an effective method to achieve high performance homogeneous dielectric elastomers (DE). Up to now, there still lacks an in-depth understanding of the effect of structure and content of these grafted dipoles on the electromechanical properties of the modified DE. In this study, three kinds of polar groups including carboxyl (COOH), hydroxyl (OH), and ester (COOCH3 ) were grafted onto polymethylvinylsiloxane (PMVS) by using a photochemical thiol-ene reaction to prepare PMVS-COOH, PMVS-OH and PMVS-COOCH3 DE. Three grafting degrees (15%, 50% and 95%) were prepared for each kind of modified PMVS. Interestingly, although the dipolar moment of COOH is higher than that of OH and COOCH3, at the same grafting degree, the dielectric constant of PMVS-OH is much higher than that of PMVS-COOCH3 and PMVS-COOH. At high grafting degree (50% and 95%), the actuated strain at a specific electric field of PMVS-OH is significantly higher than that of PMVS-COOH and PMVS-COOCH3 . The actuated train at 15 kV/mm sharply increases from 0.2% for PMVS to 9.1% for PMVS-OH with the grafting degree of 95%, higher than that of the commercial silicone DE and the new structured silicone DE reported previously. These dielectric, mechanical and actuated properties are affected by the combined effects of moment, mobility and interactions of these dipoles, which have been deeply discussed. The present study provides guidance for the preparation of high-performance homogeneous DE by rational designing the dipolar structure and content. Graphical abstract: Three different dipoles (ester, carboxyl and hydroxyl) were successfully grafted onto polymethylvinylsiloxane (PMVS) chains by using a facile one-step photochemical thiol-ene click reaction to prepare homogeneous silicone dielectric elastomer. The effects of dipole structure and content on the electromechanical and actuation performance of these silicone dielectric elastomers are deeply studied. The dielectric, mechanical and actuated properties are affected by the combined effects of moment, mobility and interactions of these dipoles.Image 1084405 Highlights: Homogeneous silicone DEs with different dipole structure and content were prepared. The interaction and mobility of dipoles were experimentally evaluated. The effect of dipoles structure on the electromechanical properties was studied. The actuated properties are affected by dipole moment, mobility and interactions.